Characterization of a Novel CdZnTe Spectrometer for Measuring Radioactivity in the Marine Environment - Siltzovalis, Georgios; Lagaki, Varvara; Madesis, Ioannis; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2023)
The scope of this study is to characterize the response of a CdZnTe spectrometer to evaluate its performance for measuring radioactivity in the marine environment. CdZnTe semiconductor detectors have never been used before for such applications. More specifically, a spectrometer with a 4 cm3 CZT crystal was studied under various scenarios, by means of Monte Carlo simulations and lab measurements. Using the Monte Carlo code MCNP5, the effect of the water’s salinity on the detector’s efficiency, as well as the ability of the sensor to localize radioactive sources in the water were examined. Futhermore, the full energy peak efficiency curve and energy resolution of the spectrometer was calculated experimentally in air. Finally, the effective volume of the CdZnTe crystal was estimated through measurements using a collimated point source of 137Cs. First results are considered satisfactory, however additional scenarios should be examined in the near future to further characterize the response of the detector.